Efficacy and Costs of Two Treatments for Diarrhoea in Calves - Che Yahya, Siti Nor (2003)
Fifty seven (57) dairy calves from small dairy holders in Serdang, Bangi and Puchong, Selangor, aged from one to 12 weeks were monitored weekly for their health status and episode of diarrhoea. The clinical parameters of each calf were also recorded until the end of the study. The blood was sampled at one-week-old for IgG, total protein, albumin and globulin levels. The calves were grouped according to their management practices. All diarrhoeic calves were dewormed with Ivomectin® (1 ml/50kg BW, SO) and Sulphadimidine® (O.5ml/kg BW, SO) as coccidiostat. The diarrhoeic calves were then chosen to be treated orally with Oral Electrolyte Salt (5gm/1 L water) at lib. (TxA) or Herbal Product (15g m/40ml water) BID (TxB). Treatment was given for 3 days. The efficacy of the treatments was measured quantitatively based on the recovery rate and body weight of the calves at the end of the study. The cost of the treatments was calculated based on the cost of the drugs used which referred to the selling cost at Universiti Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM). The cost of the disease incidence was calculated based on the cost of drugs, labour, veterinary services, dead calf and weight loss. From the study it was noted that the efficacy of the treatment was highly related to the management of the calves. Calves from the least contaminated management (MG2) showed higher recovery rate. Another factor that interfered with the treatment was nursing of the diarrhoeic calves. This was shown from worst contaminated farm (MG1) which had a better recovery rate as compared to the MG3 farm (less contamination). TxA was more effective than TxB. The cost of the treatment TxA was significantly less than treatment TxB. The cost of the disease incidence was related to the cost of the drugs used, cost of weight loss and cost of the dead calves. The IgG levels of the calves (mean age at testing was at one week old) were evaluated using Bovine IgG ELISA Quantitation Kit. Comparison was made between the management groups. It was highest from MG2 (2.95g/l) and lowest from MG3. The globulin level of MG2 (63.61 g/l) was above the normal range (27-45g/l) which indicates for higher immunoglobulin.